2022
DOI: 10.1186/s12906-022-03663-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of Bi Zhong Xiao decoction against collagen-induced arthritis rats in the early and late stages

Abstract: Background Rheumatoid arthritis (RA) is a chronic, progressive, systemic autoimmune inflammatory disease. Bi Zhong Xiao decoction (BZXD) performs multiple functions for rheumatoid arthritis (RA) treatment for decades. In this study, we aimed to study the protein alterations of BZXD in the early and late stages of RA. Methods Sprague–Dawley rats were randomly divided into the Control, collagen-induced arthritis (CIA) and BZXD groups. Clinical assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…downregulation of FASN in RA [25].Based on our informatics analysis, we confirmed the low expression of both APOD and FASN in patients with OA and RA. This finding not only extends previous research results but also emphasizes the common low expression pattern of APOD and FASN in OA and RA, providing a new perspective for understanding the shared pathological mechanisms of these two diseases and exploring potential therapeutic strategies.…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…downregulation of FASN in RA [25].Based on our informatics analysis, we confirmed the low expression of both APOD and FASN in patients with OA and RA. This finding not only extends previous research results but also emphasizes the common low expression pattern of APOD and FASN in OA and RA, providing a new perspective for understanding the shared pathological mechanisms of these two diseases and exploring potential therapeutic strategies.…”
Section: Plos Onesupporting
confidence: 74%
“…In a study by Gong et al (2023), they discovered that the CircRREB1-FASN axis alleviates the progression of osteoarthritis by inhibiting PI3K-AKT signaling mediated by FGF18 and FGFR3, leading to increased p21 expression, indirectly confirming the downregulation of FASN in OA [ 24 ]. Furthermore, He et al (2020) demonstrated that Bi Zhong Xiao decoction exerts anti-inflammatory effects in RA, primarily by increasing FASN expression and affecting fatty acid metabolism, further confirming the downregulation of FASN in RA [ 25 ].Based on our informatics analysis, we confirmed the low expression of both APOD and FASN in patients with OA and RA. This finding not only extends previous research results but also emphasizes the common low expression pattern of APOD and FASN in OA and RA, providing a new perspective for understanding the shared pathological mechanisms of these two diseases and exploring potential therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…All raw herbal voucher specimens are deposited in the author's laboratory and identified by Professor Hu Suiyu, Department of Chinese Herbal Medicine, Central South University (Changsha, China). We calculated the daily dose of BZXD herbal medicine in humans and converted it to the required daily dose in rats using the body surface area of an individual weighing 70 kg as previously described [39]. These crude drugs were immersed in distilled water for 1 h and boiled twice at 100 °C (the amount of water added was 10 times and 8 times of crude drug).…”
Section: Bzxd Preparationmentioning
confidence: 99%